2019
DOI: 10.1073/pnas.1716314116
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and molecular characterization of preterm birth

Abstract: Preterm birth (PTB) complications are the leading cause of long-term morbidity and mortality in children. By using whole blood samples, we integrated whole-genome sequencing (WGS), RNA sequencing (RNA-seq), and DNA methylation data for 270 PTB and 521 control families. We analyzed this combined dataset to identify genomic variants associated with PTB and secondary analyses to identify variants associated with very early PTB (VEPTB) as well as other subcategories of disease that may contribute to PTB. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 55 publications
6
73
0
Order By: Relevance
“…28,30 The first 40 weeks of this distribution has, of course, been targeted as a critical period in establishment of the utero-placental interface, embryonic development and transmission of signal to initiate labor onset. Investigators have observed a direct association of GA on newborn/umbilical cord DNAm 43,60,68,71,84 , including supervised algorithms designed to predict GA. 10,36,42 These studies are consistent with integrative approaches that have shown involvement of inflammatory and immune-related pathways 4,22,37 , and the larger picture of these pathways as being integral to the onset of labor. 65,66,73 Of the many potential antecedents, the literature defines a strong pathophysiological link for the causal role of inflammation on preterm birth.…”
Section: Biological Relevancesupporting
confidence: 73%
“…28,30 The first 40 weeks of this distribution has, of course, been targeted as a critical period in establishment of the utero-placental interface, embryonic development and transmission of signal to initiate labor onset. Investigators have observed a direct association of GA on newborn/umbilical cord DNAm 43,60,68,71,84 , including supervised algorithms designed to predict GA. 10,36,42 These studies are consistent with integrative approaches that have shown involvement of inflammatory and immune-related pathways 4,22,37 , and the larger picture of these pathways as being integral to the onset of labor. 65,66,73 Of the many potential antecedents, the literature defines a strong pathophysiological link for the causal role of inflammation on preterm birth.…”
Section: Biological Relevancesupporting
confidence: 73%
“…To demonstrate the translational value of single-cell RNA signatures derived from the placenta, we conducted an in silico analysis in public datasets 58, 59 to test whether the single-cell signatures could be non-invasively monitored in the maternal circulation throughout gestation (Figure 4A). Previous studies have correlated bulk mRNA expression in the maternal circulation with gestational age at blood draw 58, 60 , risk for preterm birth 59, 6163 , or both 64, 65 . First, we showed that the single-cell signatures of macrophages, monocytes, NK cells, T cells, npiCTB, and fibroblasts are modulated throughout gestation in the maternal circulation (Figure 4B-C, S19A).…”
Section: Main Textmentioning
confidence: 99%
“…Recent findings in cord blood, identified more than 8800 CpG sites associated with gestational age and the pathway analyses identified enrichment for biological processes critical to embryonic development of brain and lung tissue [ 10 ]. Moreover, several studies analyzed cord blood DNA methylation levels comparing preterm and full-term babies and reported a great number of significant differences even if the consistence among these studies has not been evaluated yet [ 11 , 12 , 13 , 14 , 15 ]. Considering the strong background regarding a potential role of epigenetics in PTB, the aim of the present study was to investigate DNA methylation differences associated with PTB at genome wide level and to evaluate consistency of results published so far.…”
Section: Introductionmentioning
confidence: 99%